Burden of proof in cases of civil liability for medical malpractice - Córdova López, Ocner (2019)
One of the main functions of the institution of civil liability is to repair the damages suffered by the victim through an economic compensation. However, for the victim of the damages produced as a result of the practice of a professional activity, to obtain compensation for the damages caused, the attributed factors, that may be subjective, that is when there is negligence; or objective, when there is not, must be accredited in trial in addition to the existence of the harm and the causal relationship. This article addresses the attributed factor, which in this case is subjective, it analyzes the burden of proof of the inexcusable fault in civil liability for medical malpractice in health institutions; more specifically, it analyzes who must prove that the harm produced to the patient was due to the inexcusable negligence or not of the health professional.